Biologically Active Compounds in Tomato Fruits Under the Application of Water–Ethanol Spirulina, Dunaliella and Chlorella Microalgae Extracts on Plants’ Leaves - Ingrīda Augšpole; Irina Sivicka; Kaspars Kampuss; Pāvels Semjonovs; Imants Missa (International Journal of Plant Biology)
This study aimed to detect an impact of water–ethanol extracts of different microalgae species—Spirulina platensis, Dunaliella salina and Chlorella vulgaris—on the accumulation of bioactive compounds in tomatoes. A treatment with the corresponding ethanol solution and pure drinking water was used as a control. Tomato cultivar ‘Belle’ F1 (Enza Zaden) was grown in a polycarbonate greenhouse, in 25 L pots filled with a peat substrate (pH KCl 5.5). The plants were sprayed weekly from germination until the start of harvesting, in total nine times. Fruits were analysed at the stage of full ripeness. Bioactive compounds’ contents such as vitamin C, titratable acidity, pH value, β-carotene, lycopene, anthocyanin, total phenols as well as total soluble solids and dry matter were analysed, and the connection between fruit mass and the taste index was determined. The influence of the tested extracts on the bioactive compounds and quality parameters of tomatoes was different, but no significant differences for most of the analysed active compounds were found, with the exception of total phenols (from 137.59 ± 1.34 to 166.93 ± 2.01 mg 100 g−1) and total soluble solids (from 3.93 ± 0.12 to 4.4 ± 0.18 °Brix). In the next research, a more detailed study about the influence of the ethanol concentration on changes in biologically active compounds should be provided.